COMPARATIVE EFFECTIVENESS OF TREATMENT OF INFLAMMATORY-PURULENT PROCESSES OF THE LIMB DISTAL SEGMENT IN PIGS - Kyrychko, B. P.; Semirenko, V. V. (Scientific Progress & Innovations, 2019)
The article materials are devoted to the development of effective, scientifically grounded treatment schemes of inflammatory-purulent processes of limb distal segment in pigs. The aim of the article is to compare the classical and experimental treatment schemes of separate nosological forms of pig limb distal segments in the comparative aspect, to define the peculiarities of medical preparation action on the blood indices of diseased pigs. The task was to conduct approbation of treatment schemes of pigs suffering from inflammatory- purulent processes of limb distal segment; to define separate morphological, biochemical, immunological indices of blood before and in the process of treatment. Clinical, hematological, immunological, and biochemical methods were used during the work. As a result, it was established that there was the increase in the number of leukocytes and the erythrocyte sedimentation rate in diseased pigs. There was a shift of the neutrophils nucleus to the left with the decrease in the number of lymphocytes in the leukogram. There was also the decrease of the immunity activity in pigs. Immunodeficiency was due to a low content of immune defense components and dysproteinemia. Increasing the level of hexoses, glycosaminoglycans, glycoproteins and the concentration of sialic acids was registered in pigs suffering from inflammatory-purulent processes, which indicated at involving the structural elements of connective tissue of the locomotorium in the inflammatory process. The results of the conducted studies testify that the diseased animals have the increased content of malonic dialdehyde and catalase activity, which is stipulated by activating the antioxidant system. The deficit of calcium, phosphorus, vitamin A, and β-carotene was also registered. Taking into account the obtained results of laboratory tests of the diseased animal’ blood, we suggested the treatment scheme that included using medicinal preparations of pathogenetic action. Comparing the classical and experimental treatment schemes, the peculiarities of medicinal preparations’ action on the blood indices of the diseased pigs were established. In segmenticular, “Trifuzol 1 %” preparation increases the number of the immune system specific components (T-cells and B-lymphocytes, the population of T-cells, NK-cells), stimulates the metabolism of connective tissue and the antioxidant system of the body on the whole. Morphological, biochemical, and immunological blood indices are also normalized, the recovery of pigs suffering from purulent- inflammatory processes of the limb distal segment quickens.